2002
DOI: 10.1080/09593332508618425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogen Peroxide Oxygen Transfer Tests on the Performance of the Biological Nutrient Removal Process

Abstract: Knowledge of in-process oxygen transfer is essential to the optimum design and operation of aeration systems in activated sludge processes. In this study, non-steady state H2O2 oxygen transfer tests were performed in a laboratory scale, University of Cape Town configuration biological nutrient removal process (BNR) to measure the in-process oxygen transfer rates. Given the small quantity (about 1 ml @30% concentration) of H2O2 used in the aerobic reactor with a mixed liquor volume of 161 (total system working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition to the surprisingly high oxygen transfer parameters, the H2O2 addition resulted in rapid increases in ORP and pH and such changes potentially alter the metabolic functioning of microorganisms (Mahendraker et al 2002). This test also led to a loss in process efficiency in terms of COD, ammonia and phosphorus removal by the process (Mahendraker et al 2002, In press).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the surprisingly high oxygen transfer parameters, the H2O2 addition resulted in rapid increases in ORP and pH and such changes potentially alter the metabolic functioning of microorganisms (Mahendraker et al 2002). This test also led to a loss in process efficiency in terms of COD, ammonia and phosphorus removal by the process (Mahendraker et al 2002, In press).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of hydrogen peroxide on the activated sludge system to measure in process oxygen transfer was studied (Mahendraker et al, 2002). It was found that small amounts of hydrogen peroxide (1 ml at 30% concentration) inhibited carbon, nitrogen, and phosphorus removal in the activated sludge system.…”
Section: Combined Nitrogen and Phosphorus Removal A Comparison Studymentioning
confidence: 99%
“…After total ammonia oxidation in this reactor, a new ammonia addition re‐established the plateau, with the nitrification process remaining inhibited in reactor 1. The effect of H 2 O 2 addition on process performance observed by Mahendraker et al (2002) may possibly be a result of the duration or mass of the H 2 O 2 addition.…”
Section: Effect Of Hydrogen Peroxide Addition On the Process Performamentioning
confidence: 99%